2014
DOI: 10.15287/afr.2014.214
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between leaf traits and morphological attributes in one-year bareroot Fraxinus angustifolia Vahl. seedlings

Abstract: Leaf traits were investigated as morphological attributes for quality estimation of one-year-old bareroot seedlings of Fraxinus angustifolia Vahl. Leaf traits (number of simple -NSL and compound leaves -NCL, leaf average -ALA and total area -TLA and leaf area ratio -LAR) show similar relations to morphological attributes, the strongest to shoot growth (height -HT, root collar diameter -DIA and shoot dry weight -SDW). Increases of seedling morphological attributes are strongly related to increases of ALA. Given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For instance, wood density is a good predictor of individual tree diameter increments (Wright et al 2010), and correlates con-sistently with the biomass increment (Finegan et al 2015). Besides wood density, specific leaf area is known to be related with the intensity of plant respiration and photosynthesis (Ivetić et al 2014, Weraduwage et al 2015, and thus plant growth. In the infancy of its growth, a plant would tend to allocate more resources to leaves so that to allow maximum interception of light and favour fixation of large amounts of C from atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, wood density is a good predictor of individual tree diameter increments (Wright et al 2010), and correlates con-sistently with the biomass increment (Finegan et al 2015). Besides wood density, specific leaf area is known to be related with the intensity of plant respiration and photosynthesis (Ivetić et al 2014, Weraduwage et al 2015, and thus plant growth. In the infancy of its growth, a plant would tend to allocate more resources to leaves so that to allow maximum interception of light and favour fixation of large amounts of C from atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…e RGR at 9-12 WAT had a significant positive correlation with NAR at 4-8 WAT and 8-12 WAT. Previous research has shown that NAR is the most critical predictor of RGR [49]. Fast-growing plants always have a high NAR, and plants with high assimilation rates always grow fast.…”
Section: Productionmentioning
confidence: 98%
“…Leaf area ratio determines light interception and is an essential parameter in determining plant productivity [48]. It expresses the potential for photosynthesis per unit of plant biomass [49]. e LAR was measured at 0-4 WAT, 4-8 WAT, and 8-12 WAT.…”
Section: Leaf Area Ratio (Lar)mentioning
confidence: 99%
“…The grading of particles (seed material with small grain size) by spectrometric properties [5], is positioned as an alternative to traditional methods of separation (using a sieve, separation, aspiration devices). The combination of this, as well as the seeds provenance and of nursery production method [6] will further improve the seedlings quality. The variety of technical means implementing optical technology leads to the need for analytical studies of their operational parameters [4].…”
Section: Introductionmentioning
confidence: 99%